Training and assistance on the use of village administration management system using OpenSID in Sukatani Village - Aries Suharso; Gusganda Suria Manda; Chaerur Rozikin; Mayasari Mayasari (University of Merdeka Malang, 2022)
Sukatani Village, Compreng Sub-District, Subang District in carrying out village administration services still uses Microsoft Word in making village correspondence then the letter number is recorded in the village ledger and the Sukatani village population data is still stored in excel form. The problem is that typos often occur, it takes a long time to search for correspondence files and cannot present population data accurately. This problem can be overcome by using a village administration management system that will be used in Sukatani village. The system was developed using the OpenSID framework which is licensed and free to use and developed for village purposes. In order for the village apparatus to easily use the village administration management system, training and assistance is needed. The training and mentoring is carried out by dividing into two groups and each group is accompanied by a trainer so that the training for village officials can run smoothly and well. The result of this service activity is that the village administration management application and village apparatus can use the application well so that the application can be used continuously to improve village administration services to Sukatani villagers.